Functional expression of P2 purinoceptors in a primary neuroglial cell culture of the rat arcuate nucleus. (7th July 2016) - Pollatzek, Eric; Hitzel, Norma; Ott, Daniela; Raisl, Katrin; Reuter, Bärbel; Gerstberger, Rüdiger
Highlights: Establishment of a differentiated neuroglial primary cell culture system of the early postnatal rat arcuate nucleus (ARC). Calcium imaging experiments indicate expression of P2X2 and P2Y1 purinoceptors in ARC neurons and/or astrocytes. ARC neurons and astrocytes can be subdivided into partially temperature-dependent low and high desensitization groups. Competitive binding assays with the radioligand [ 35 S]dATPαS support functional purinoceptor expression in rat hypothalamus. Abstract: The arcuate nucleus (ARC) plays an important role in the hypothalamic control of energy homeostasis. Expression of various purinoceptor subtypes in the rat ARC and physiological studies suggest a modulatory function of P2 receptors within the neuroglial ARC circuitry. A differentiated mixed neuronal and glial microculture was therefore established from postnatal rat ARC, revealing neuronal expression of ARC-specific transmitters involved in food intake regulation (neuropeptide Y (NPY), proopiomelanocortin (POMC), tyrosine hydroxylase (TH)). Some NPYergic neurons cosynthesized TH, while POMC and TH expression proved to be mutually exclusive. Stimulation with the general purinoceptor agonists 2-methylthioadenosine-5′triphosphate (2-MeSATP) and ATP but not the P2X1/P2X3 receptor subtype agonist α, β-methyleneadenosine-5′triphosphate (α, β-meATP) induced intracellular calcium signals in ARC neurons and astrocytes. Some 5–10% each of 2-MeSATP responsive neurons expressed POMC, NYP or TH. Supporting the calcium imaging data, radioligand binding studies to hypothalamic membranes showed high affinity for 2-MeSATP, ATP but not α, β-meATP to displace [α- 35 S]deoxyadenosine-5′thiotriphosphate ([ 35 S]dATPαS) from P2 receptors. Repetitive superfusion with equimolar 2-MeSATP allowed categorization of ARC cells into groups with a high or low (LDD) degree of purinoceptor desensitization, the latter allowing further receptor characterization. Calcium imaging experiments performed at 37 °C vs . room temperature showed further reduction of desensitization. Agonist-mediated intracellular calcium signals were suppressed in all LDD neurons but only 25% of astrocytes in the absence of extracellular calcium, suggestive of metabotropic P2Y receptor expression in the majority of ARC astrocytes. The highly P2Y1 -selective receptor agonists MRS2365 and 2-methylthioadenosine-5′diphosphate (2-MeSADP) activated 75–85% of all 2-MeSATP-responsive ARC astrocytes. Taking into consideration the high potency to dose-dependently stimulate ARC cells of the LDD group, the high affinity for rat P2X(1–3) and low affinity for rat P2X4, P2X7 and P2Y receptor subtypes except P2Y1 and P2Y13, the agonist 2-MeSATP primarily acted upon P2X2 and P2Y1 purinoceptors to trigger intracellular calcium signaling in ARC neurons and astrocytes.